Mudanças na alimentação de mulheres após orientações de perfis de alimentação em redes sociais - (:unkn) unknown (Universidade Federal do Pampa, 2023)
The media, such as social networks, influence people's eating behavior. Whether through promises of weight loss with miracle diets, the dissemination of certain food fads or even the indication of foods as ""culprits"" for a certain state of health or body (in)satisfaction, networks can change the eating habits of their consumers. The aim of this study was to find out whether the use of social networks is associated with changes in the behavior or food choices of mothers attending a natural products fair in Uruguaiana-RS. The fair where the research was carried out takes place on Sundays in a square located in the city center and is open to the public. Data was collected between May and July 2023. A questionnaire was used to collect the data, with objective questions divided into three parts: demographic data (name, age), questions about attending the fair and about the use of social networks (whether they follow food-related profiles; whether they have made any changes to their eating habits as a result of the influence of the profiles). It was possible to assess that 26 participants (78.8%) included new foods or habits in their eating routine after regularly following food-related profiles. Some of the foods mentioned in the survey as being included in the new routine were cauliflower, broccoli, yams, oatmeal, lactose-free milk, among others, in the form of preparations or recipes. It was also found that 60.6% (n=20) of the women had removed some foods/habits from their daily lives, such as: avoiding sugar for children under two years old, removing ready-made spices due to their high sodium and additive content and replacing them with natural spices, removing processed foods such as filled cookies, snacks, cake mixes, sausages and soft drinks. A reduction in the use of white wheat flour, previously considered the only option for preparing recipes, was also reported. The responses did not show behaviors such as restrictive diets or those based on nutritional terrorism, but rather changes that could bring benefits to consumers' health, especially with regard to reducing consumption of ultra-processed foods and increasing consumption of vegetables. This study found that the profiles followed by the study participants provided correct information on food and health and influenced positive changes in eating behavior and/or promoted healthier food choices by the women.
Changes in women's diets following guidance from food profiles on social media
Keywords: Alimentação adequada e saudável; Mídias sociais; Consumo alimentar; Eating habits; Social media; Food consumption; CIENCIAS DA SAUDE